2006
DOI: 10.1016/j.chembiol.2006.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Glycosylation Pathways and the Cell Cycle: Sugar-Dependent Activity of Butyrate-Carbohydrate Cancer Prodrugs

Abstract: Short-chain fatty acid (SCFA)-carbohydrate hybrid molecules that target both histone deacetylation and glycosylation pathways to achieve sugar-dependent activity against cancer cells are described in this article. Specifically, n-butyrate esters of N-acetyl-D-mannosamine (But4ManNAc, 1) induced apoptosis, whereas corresponding N-acetyl-D-glucosamine (But4GlcNAc, 2), D-mannose (But5Man, 3), or glycerol (tributryin, 4) derivatives only provided transient cell cycle arrest. Western blots, reporter gene assays, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
107
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(117 citation statements)
references
References 55 publications
10
107
0
Order By: Relevance
“…n-Butyrate, a naturally occurring short-chain fatty acid, is a well known histone deacetylase (HDAC) inhibitor [37]. In recent years, HDAC inhibition has attracted much attention for the development of anticancer drugs because HDAC inhibitors are able to disrupt cell cycle progression or selectively induce apoptosis via depression of certain genes [38][39][40][41]. Thus, the butyrate species liberated from the hydrolysis of these butyrylated derivatives may have contributed to the apparently higher potency of these compounds.…”
Section: Evaluation Of Biological Activitymentioning
confidence: 99%
“…n-Butyrate, a naturally occurring short-chain fatty acid, is a well known histone deacetylase (HDAC) inhibitor [37]. In recent years, HDAC inhibition has attracted much attention for the development of anticancer drugs because HDAC inhibitors are able to disrupt cell cycle progression or selectively induce apoptosis via depression of certain genes [38][39][40][41]. Thus, the butyrate species liberated from the hydrolysis of these butyrylated derivatives may have contributed to the apparently higher potency of these compounds.…”
Section: Evaluation Of Biological Activitymentioning
confidence: 99%
“…In follow-up studies, our laboratory more thoroughly characterized the SCFA effects of butyrate appended to several monosaccharides, including ManNAc (Bu 4 ManNAc), mannose (Bu 5 Man), and GlcNAc (Bu 4 GlcNAc). We found that each of these hybrid compounds had the canonical activities expected from SCFAs, including histone deacetylase inhibition, up-regulation of p21 gene expression, and transient cycle-cell arrest that resulted in 3-to 5-day growth inhibition of cancer cell lines [73]. Only Bu 4 ManNAc, however, induced apoptosis in a variety of cancer lines.…”
Section: Unanticipated Effects Of Moementioning
confidence: 92%
“…10-5) have the potential to exacerbate perturbations to cellular physiology. To explain briefly, in the past, SCFAs such as acetates have been regarded as innocuous delivery agents; in reality, profound biological activities can be realized when using SCFA-sugar hybrids [12,[71][72][73]. For example, toxicity has long been associated with acetylation of sugars used in MOE, and although it is generally mild and not usually manifest in vivo, the underlying molecular mechanisms proved to be highly intriguing, as various N -acyl modifications of ManNAc were found to "tune" toxicity.…”
Section: Unanticipated Effects Of Moementioning
confidence: 99%
See 1 more Smart Citation
“…In the 1970s, chemists have synthesized Nglycoside compounds and proved that they had the anti-tumor activity. Japanese scholar Sampathkumar et al [1] have studied the anti-tumor activity of mannose with the hydroxyl group in C-2 being substituted by different amide groups. Nicolas Bridiau in France has confirmed that N-glycoside compounds have better stability with respect to glycosidase compared with O-glycoside compounds.…”
mentioning
confidence: 99%